L'apiculture - Paterson , David Peter (éditions Quae, 2008)
This book, through its clear explanatory text and admirable illustrations, skilfully lays out the elements of good practice in tropical beekeeping. It explains both traditional techniques using low-cost hives and more advanced methods, pointing out the most appropriate system for the level of investment the beekeeper wishes to make. Existing beekeepers wishing to improve their techniques and those looking to start a new beekeeping enterprise will find the book invaluable.